PENERAPAN PROGRAM SUPERVISI AKADEMIK TERHADAP PENINGKATAN KINERJA GURU - Iim Siti Halimah (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2020)
This madrasah action research aims to determine the implementation of academic supervision programs implemented by madrasah principals to improve teacher performance in implementing exploration-based learning, elaboration, and confirmation. The form of research used a madrasah action research design. The subject of this research is the teacher who is the homeroom teacher of class 1 to grade 6, totaling 12 people. The research activity was carried out in two cycles. The time of research activities in the odd semester 2019/2020 academic year, starting from August to October 2019. Based on the results of the study, it is known that the average performance score of the twelve teachers in implementing learning in pre-cycle activities is 75.05; the average value in cycle I activities was 81.80 (an increase of 6.75); and the average value in cycle II was 88.73 (an increase of 6.93), which means that there is an increase in teacher performance in the implementation of learning. The results showed that the implementation of the academic supervision program could improve teacher performance in implementing exploration-based learning, elaboration, and confirmation.